Seleção e expressão de caracteres componentes da aparência e rendimento de tubérculos na geração de plântulas de batata - Cerioli, Murilo de Farias (2013)
Improvements in methods of selection are extremely important for breeding programs because the market requires speed and efficiency in development new cultivars. In potato breeding, the elimination of genotypes with undesirable characteristics through early generation selection avoids that inferior genotypes be taken to the field. Selection for some traits in the seedling generation saves considerable resources and improves the quality of the population carried to the field. The aim of this study was to investigate in the seedling generation the influence of pot size on the expression of general appearance and yield of tubers and the selection efficiency. The study consisted of two generations of seedlings obtained from ten different crosses grown in the greenhouse in three different pot sizes during the autumn and spring. A first clonal generation was derived from autumn seedlings and planted in the field. Traits components of tuber appearance and yield were measured and trait correlations within seedling generation and between generations were determined. The results show that pot size influences trait expression and that early selection in the seedling generation is a viable option for many tuber appearance and yield component traits. Most traits are better expressed in large pots except skin roughness which showed more reticulated skin tubers in small pots. Skin roughness, tuber shape, tuber weight and number of tubers are more efficient for selection in the seedling generation.